Correlation between B-Type Natriuretic Peptide and Functional/Cognitive Parameters in Discharged Congestive Heart Failure Patients - Laura Leto; Marzia Testa; Mauro Feola (International Journal of Endocrinology)
The determination of B-type natriuretic peptides (BNP) may have a role in the diagnosis of heart failure (HF) or guiding HF therapy. This study investigated the role of BNP determination in a cohort of elderly patients admitted to hospital with acute decompensated HF and its correlation with main demographic, clinical, and instrumental data and evaluated possible association with major outcome such as mortality or readmission after a 6-month period of follow-up. Methods. From October 2011 to May 2014 consecutive patients admitted to our unit with symptoms of acute HF or worsening of chronic HF entered the study collecting functional, echocardiographic, and hydration parameters. Correlation between BNP and main parameters was analysed, as well as the mortality/6-month readmission rate. Results. In 951 patients (mean age 71 ys; 37% females) a positive correlation was obtained between BNP and age, creatinine levels, NYHA class at admission and discharge, and levels of hydration; an inverse, negative correlation between BNP and sodium levels, LVEF, distance performed at 6MWT at admission and at discharge, and scores at MMSE at admission and discharge emerged. BNP levels at admission and at discharge were furthermore clearly associated with mortality at 6 months (Chi-square 704.38, p=0.03) and hospital readmission (Chi-square 741.57, p<0.01). Conclusion. In an elderly HF population, BNP is related not only with clinical, laboratory, and instrumental data but also with multidimensional scales evaluating global status; higher BNP levels are linked with a worse prognosis in terms of mortality and 6-month readmission.